2009
DOI: 10.1007/s10683-009-9222-z
|View full text |Cite
|
Sign up to set email alerts
|

Promoting justice by treating people unequally: an experimental study

Abstract: Which inequalities among individuals are considered unjust? This paper reports the results of an experiment designed to study distributive choices dealing with arbitrarily unequal initial endowments. In a three-person distribution problem where subjects either know or do not know their endowments, we find impartial behavior to be a stable pattern. Subjects either compensate for initial inequalities fully or not at all in both conditions, and they do so more often when they do not know their endowment than when… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 22 publications
2
11
0
Order By: Relevance
“…This literature has shown that different people adopt different fairness principles in distribution situations (Konow, 2000;Frohlich et al, 2004;Cappelen et al, 2007;Becker and Miller, 2009). Such a multiplicity of fairness principles can also be expected in this experiment.…”
Section: Introductionsupporting
confidence: 74%
See 1 more Smart Citation
“…This literature has shown that different people adopt different fairness principles in distribution situations (Konow, 2000;Frohlich et al, 2004;Cappelen et al, 2007;Becker and Miller, 2009). Such a multiplicity of fairness principles can also be expected in this experiment.…”
Section: Introductionsupporting
confidence: 74%
“…Note that the exchange rate is 3 tokens 1 GBP. Frohlich et al (2004) and Becker and Miller (2009) find a similar rule of behavior.…”
Section: Experimental Design and Proceduresmentioning
confidence: 60%
“…Other studies replicated this result, but nevertheless showed that equality of opportunity is not a full substitute for equality of outcomes (Becker and Miller 2009;Krawczyk and Le Lec 2010). It was also shown that many people are willing to sacrifice money to reject allocations that are brought about by procedures that are extremely biased (Bolton et al 2005;Karni et al 2008).…”
Section: Literature Reviewmentioning
confidence: 96%
“…Carlsson, Guptaz, and Johansson-Stenman (2003) reported using economic experiments that Indian students are strongly inequality averse when choosing from behind a veil of ignorance, with around one-fifth choosing income distributions closest to Rawlsian notion of equality, which is in line with previous results from Sweden by JohanssonStenman, Carlsson, and Daruvala (2002) (cf. also Becker and Miller 2009). Although there is much discussion on the external validity of economic experiments like these (List and Shogren 1998), in particular those that deal with moral and public issues, their shortcomings seem to be more related to magnitudes (size of the effects detected) than qualitative insights (nature of the relationships observed) (Levitt and List 2007), and their results, on the whole, present reasonably solid degree of validity (Chang, Lusk, and Norwood 2009).…”
Section: A New Relationship Between Education and Inequality: Furthermentioning
confidence: 99%